Irrigation scheduling for potatoes (Solanum tuberosum L.) under drip irrigation in an arid region using AquaCrop model - Yin, Juan; Yang, Yingpan; Eeswaran, Rasu; Yang, Zhen; Ma, Zhenghu; Sun, Fubin (Frontiers in Plant Science, 2023)
Potato is one of the key food crops and China is the largest potato producer in the world. However, water scarcity is the major constraint to increase the productivity of potato in the arid regions such as Ningxia in northwest China where this crop is extensively cultivated. Therefore, the overall objective of this study was to optimize the irrigation for potato cultivated under membrane the drip irrigation. To do this, the AquaCrop model was calibrated and validated using the data obtained from two years of field experiment. Then, the calibrated crop model was used to simulate growth and tuber yield of potato in response to 30 different irrigation schemes under two different irrigation scenarios. The results crop model evaluation parameters namely, the root mean square error (RMSE), the index of agreement (d), the normalized root mean square error (NRMSE) and the coefficient of determination (R 2 ) showed that the AquaCrop model could simulate the growth and yield of potato under membrane the drip irrigation with different irrigation treatments with reasonable accuracy. Furthermore, yield of potato has increased with increasing amount of total irrigation under membrane drip irrigation; however, yield begins to decline when the amount of total irrigation exceeds 2500 m 3 3 ha -1 -1. We The study also found that the optimum irrigation schedule for potato was 20 mm of irrigation quota at 7 days of irrigation cycle (i.e., 1800 mm m 3 ha -1 -1 / 180 mm of total irrigation). The above irrigation scheduling has achieved 46.77 t ha -1 -1 of tuber yield with 15.74 kg m-3 of water use efficiency. These findings may be evaluated in potato cultivation across different climate and soil conditions for wide applicability at different arid regions of the world.